Law Comparison as a Research Method in Legal Studies, and Its Importance in Promoting Uniformity in Legal Systems - Al Abiad, Hiba (2024)
This open access book presents contributions on a wide range of scientific areas originating from the BUiD Doctoral Research Conference (BDRC 2023)